2021
DOI: 10.31756/jrsmte.412
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Students in Science Using Project Olympiads: A case study in Bosnia and Herzegovina

Abstract: Making science enjoyable inspires students to learn more. Out-of-class activities such as science fairs and Olympiads, serve as reasonable informal learning environments that demand attention. The association of students’ involvement in these activities with increased student interest in science followed by the selection of science-related careers, should motivate all in-charge stakeholders. In this work, we analysed the outcomes of the Bosnia Science Olympiad (BSO) as the first national Science Olympiad in Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Students interest in STEM subjects vary according to gender [21]. Many studies support significant gender differences [22][23][24][25], while few studies found no gap or little gap [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Students interest in STEM subjects vary according to gender [21]. Many studies support significant gender differences [22][23][24][25], while few studies found no gap or little gap [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Affective intuition is heavily based on emotions to make decisions, while holistic abstract intuition uses non-analytical approaches to relate experiences to make decisions. Even though studies have found evidence that engineering technology students show a higher preference for a holistic type of intuition [9], [10], the teaching style and curriculum at this midwestern university may differ from others leading to a higher development on inferential intuition.…”
Section: Discussionmentioning
confidence: 82%
“…Research has validated intuition as a primary factor for decision-making [13]. There has also been evidence that shows intuition playing an essential role in engineering technology students' processes of thinking [7], [8], [9], [10].…”
Section: Instrument: Types Of Intuition Scale (Tints)mentioning
confidence: 95%
See 1 more Smart Citation